2002
DOI: 10.1038/sj.onc.1205768
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a 500 kb region on 17q25 and the exclusion of candidate genes as the familial Tylosis Oesophageal Cancer (TOC) locus

Abstract: The locus for a syndrome of focal palmoplantar keratoderma (Tylosis) associated with squamous cell oesophageal cancer (TOC) has been mapped to chromosome 17q25, a region frequently deleted in sporadic squamous cell oesophageal tumours. Further haplotype analysis described here, based on revised maps of marker order, has reduced the TOC minimal region to a genetic interval of 2 cM limited by the microsatellite markers D17S785 and D17S751. Partial sequence data and complete physical maps estimate the actual size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 40 publications
0
16
0
1
Order By: Relevance
“…In a cancer context, CYGB has been implicated as a TSG in familial tylosis with esophageal cancer and sporadic squamous cell esophageal carcinoma (23)(24)(25)(26), and there is preliminary evidence suggesting tumour suppressor activity of CYGB based on the observation of an inverse relationship between CYGB expression and colony formation in NSCLC and breast cancer cell lines (29). Recently, a CYGB knockout mouse has been generated and it was found that, upon exposure to N,N-diethylnitrosamine, CYGB-deficient mice were more susceptible to liver and lung cancer development, further supporting a role for this gene in cancer (78).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a cancer context, CYGB has been implicated as a TSG in familial tylosis with esophageal cancer and sporadic squamous cell esophageal carcinoma (23)(24)(25)(26), and there is preliminary evidence suggesting tumour suppressor activity of CYGB based on the observation of an inverse relationship between CYGB expression and colony formation in NSCLC and breast cancer cell lines (29). Recently, a CYGB knockout mouse has been generated and it was found that, upon exposure to N,N-diethylnitrosamine, CYGB-deficient mice were more susceptible to liver and lung cancer development, further supporting a role for this gene in cancer (78).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, our candidate interval overlaps the familial tylosis with esophageal cancer locus (23). Although mutation analyses of RHBDF2 and CYGB did not identify any disease associated mutations, decreased expression of CYGB was observed in familial tylosis with esophageal cancer samples and cell lines derived from sporadic squamous cell esophageal carcinomas (23)(24)(25)(26). Further characterization of CYGB showed alterations in promoter CpG methylation in sporadic, but not familial tylosis with esophageal cancer (26).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…do zwiększonej aktywacji receptorów dla naskórkowego czynnika wzrostu (ang. epidermal growth factor -EGF), która może mieć udział w patogenezie raków przełyku [7,8].…”
Section: Zespoły Uwarunkowane Genetycznieunclassified
“…The tylosis oesophageal cancer gene (TOC) is localized to a small region on band 17q25, a region frequently deleted in persons with sporadic squamous cell oesophageal tumours Risk et al, 2002). This region contains 5'end of uncharacterized (FM8) gene, which is likely non coding RNA, a promoter of another gene and the whole cytoglobin gene (Langan et al, 2004).…”
Section: Notementioning
confidence: 99%